Culture-Independent Analysis of Bacterial Communities in the Gut of Rice Water Weevil (Coleoptera: Curculionidae). (1st May 2014) - Lu, Fang; Kang, Xiaoying; Lorenz, Gus; Espino, Luis; Jiang, Mingxing; Way, Michael O
Abstract: Gut bacteria play important roles in the biology of insects. In this study, gut bacterial communities were investigated in the rice water weevil, Lissorhoptrus oryzophilus Kuschel (Coleoptera: Curculionidae), which is a serious pest in rice growing-areas of the United States and some Asian countries. Overwintered female adults were collected from rice plants in five geographic locations: Beaumont, TX; Colt, AR; and Biggs, CA; in the United States, and Tanghai of Hebei and Yueqing of Zhejiang in China. Using polymerase chain reaction, bacterial 16S rRNA clone libraries were constructed. From the libraries, we identified 19 bacterial phylotypes (operational taxonomic units, OTUs). Of them, only 3–5 OTUs were identified in each population, except in the Beaumont weevils, which had 10 OTUs. The OTUs were affiliated with the bacteria in six classes of four phyla: α-, β-, γ-proteobacteria, Bacilli, Sphingobacteria, and Actinobacteria, with the γ -proteobacteria being the richest. Bacteria of the genera Pantoea and Wolbachia were detected in all weevil populations examined. There were also some bacteria that were specifically detected in certain locations but had a high relative abundance, such as the ones matched to Enterobacter oryzae, Lactococcus lactis, and Rickettsia felis. Geographic variations were found among bacterial communities in their richness, diversity, and evenness. This was the first study depicting a detailed profile of bacterial communities in L. oryzophilus, and the results provide important information for future studies on the bacterial functions, mutual interactions, and use for developing a biocontrol technique against this weevil.